Phytoremediation potential of tobacco and Brassica juncea exposed to Cd stress - Alves, S (2012)
Cd is the fifth most toxic metal to vertebrates and the fourth most toxic metal to vascular plants. A plant suitable for phytoremediation should especially possess the following characteristics: 1) ability to accumulate metals preferably in the aboveground parts, 2) tolerance to metal accumulated, 3) fast growth and high biomass and 4) easy harvestability. Plants usually experience oxidative stress when they are exposed to Cd and other heavy metals thus, changes of the activities of major antioxidant enzymes (SOD; GPX, APX, CAT and GR) were investigated.